Analisa Potensi Bahaya dan Upaya Pencegahan Kecelakaan Kerja Dengan Job Safety Analisys (JSA) Pada Divisi Pencucian di PT “X” - Siti Rohmah; Kuswinarti Kuswinarti (Proceedings Series on Physical & Formal Sciences, 2021)
The work process in the washing division of the "X" Company consists of three kinds of processes: washing, squeezing and drying. All of these work processes involve interactions between workers, raw materials, equipment and the environment. These interactions can create hazards and risks to both health and accident risks if they are not carried out according to the correct procedures and steps. The purpose of this study is to determine the potential hazards and risk rating in order to provide recommendations for their control in the washing division of the "X" Company. The research method is observational, which is only observing objects without controlling any variables. The steps taken are to identify and analyze the existing hazards and the risks that may occur so that analysis of potential hazards, types of accidents that may occur and recommendations for their control is needed. The research results show that the potential hazards in the washing division are 52, consisting of 46 ergonomic hazards and 6 chemical hazards. On this basis, recommendations for control have been prepared to prevent accidents that must be carried out.